Risk factors associated with pulmonary exacerbations in pediatric patients with cystic fibrosis (2019)
ABSTRACT: Introduction. Cystic fibrosis patients develop pulmonary exacerbations (PEs) that require intravenous treatment. The objective of this study was to determine the risk factors associated with PEs and establish the percentage of patients who failed to recover their lung function. Population and methods. Observational, retrospective, cohort study. The medical records of cystic fibrosis patients seen at Hospital de Niños Ricardo Gutiérrez in 2013 were reviewed. Patients were divided into group 1, with PE (Fuchs criteria), and group 2, without PE. Age, sex, p.F508del mutation, percentage of baseline forced expiratory volume in the first second, baseline body mass index Z-score, chronic Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus and Burkholderia cepacia complex colonization (Leeds criteria), percentage of cystic fibrosis-related diabetes, and recovery of baseline forced expiratory volume in the first second were recorded. Results. A total of 117 patients were included. Group 1: 50, group 2: 67 patients. PEs were associated with a lower body mass index Z-score (RR: 1.45; p = 0.002), p.F508del mutation (RR: 3.23; p = 0.05), and chronic Burkholderia cepacia complex (RR: 3.69; p = 0.002), Pseudomonas aeruginosa (RR: 1.89; p = 0.01) and methicillinresistant Staphylococcus aureus colonization (RR: 2.32; p = 0.002). Twenty-four percent of patients failed to recover their lung function. Conclusions. The presence of the p.F508del mutation, a poor nutritional status, and chronic colonization were the risk factors for exacerbation. A fourth of patients failed to recover their lung function.